Luminescence and temperature sensing properties of Dy3+-doped YPO4 glass ceramic. Issue 6 (15th March 2023) - Huang, WenJun; Lei, JiaHui; Chen, YiHang; Chen, JunYu; Li, Yi; Chen, LiPing; Guo, Hai
Abstract: Dy 3+ -doped YPO4 glass ceramic (GC) samples were produced by melt-quenching method and followed heat-treatment. Differential scanning calorimetry curve, X-ray diffraction patterns, Fourier transform infrared spectra, transmission electron microscope images were used to analyze the structure of YPO4 GC. The optimal GC sample is GC565 (sample heat-treatment at 565 °C for 2 h). The fluorescence intensity ratio ( FIR ) of emissions from 4 I15/2 and 4 F9/2 to 6 H15/2 of Dy 3+ in YPO4 GC565 excited by 350 nm light was used to detect temperature. The efficient energy difference between 4 I15/2 and 4 F9/2 levels is 1296 cm −1 and the maximum relative sensitivity achieves 2.03 %K −1 at 303 K. Our work indicates that Dy 3+ -doped YPO4 GC have a prospective application in optical temperature sensing.